Penyuluhan Gizi untuk Meningkatkan SDM Masyarakat dan Pencegahan Stunting di Dusun Semalang Desa Kaloran Temanggung - Salis Irvan Fuadi; Fatimah Azzahra; Vili Vili; Sugeng Arif; Irfan Aditya; Wakhidiriono Wakhidiriono; Ariesta Luciana Hendrika; Gianiza Faqih Pramana; Rofiyanti Rofiyanti (jurnal ABDIMAS Indonesia, 2025)
This study aims to measure the effectiveness of nutrition counseling in improving community understanding of stunting prevention in Semalang Hamlet, Kaloran Village. The research method uses a qualitative approach, qualitative data obtained through in-depth interviews. This qualitative research was conducted on 21 mothers and children in Semalang Hamlet. The results of the interviews showed a significant increase in participants' understanding of the importance of exclusive breastfeeding, complementary feeding, and sanitation. However, there are still obstacles in implementing infant feeding practices, especially in determining the right portion to meet children's nutritional needs. Factors such as limited knowledge about balanced nutrition and lack of access to nutritious food were the main barriers. This study concludes that nutrition counseling is a good first step, but needs to be combined with more comprehensive interventions, such as cooking demonstrations, home visits, and availability of nutritious food at the community level.